Analisis Kontribusi, Pertumbuhan, Efisiensi dan Efektivitas Retribusi Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten Kolaka - Ilham, Surianto; Syahrir, Sasmita Nabila; Supardi, Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the magnitude of the contribution, the rate of retribution growth, and the efficiency and effectiveness of the tourism sector's retribution on the Kolaka Regency's original revenue in 2016–2020. Researchers used descriptive research with a qualitative approach. The data analysis techniques used are the contribution ratio, growth ratio, efficiency ratio, and effectiveness ratio. The results of this study indicate that the contribution of the tourism sector's retribution to local revenue in Kab. Kolaka is relatively low, with an average of 0.72% per year. 2016 was recorded as the lowest contribution, and 2019 as the highest contribution. The growth rate of tourism retribution in Kolaka Regency is an average of 25.55% per year. The highest growth rate was recorded in 2018. The efficiency level of tourism retribution in Kolaka Regency was recorded in 2016–2020 as inefficient, with an average of 46.63% per year. The level of effectiveness of the Kolaka Regency tourism levy recorded for 2016-2020 is quite effective, with an average of 93.134% per year.